Deformation characteristics and peak temperatures of the Sanbagawa Metamorphic and Shimanto Accretionary complexes on the central Kii Peninsula, SW Japan. (1st August 2021) - Shimura, Yusuke; Tokiwa, Tetsuya; Mori, Hiroshi; Takeuchi, Makoto; Kouketsu, Yui
Graphical abstract: Highlights: Deformation and temperature were examined in Cretaceous subduction complexes. The complex at 280–440 °C records exhumation-related deformation. The complex at 280–290 °C records accretion- and exhumation-related deformations. The two deformations occurred in different tectonic settings in the subduction zone. The generation of exhumation-related deformation involved ridge approach. Abstract: Structural analyses based on field survey and peak-temperature estimations using Raman spectra of carbonaceous-material thermometry were conducted for the Cretaceous subduction complexes on the central Kii Peninsula, southwest Japan, where there is a direct contact region between the Sanbagawa high- P /low- T Metamorphic Complex (MC) and the Shimanto Accretionary Complex (AC). In the study area, the Kosoku, Iro, and Mugitani complexes are arranged in descending order of structural position. The Kosoku and Iro complexes record exhumation-related deformation, which produced schistosity, stretching lineation, and folds, and peak temperatures of 280–440 °C. In contrast, the Mugitani Complex records both earlier accretion-related deformation which produced block-in-matrix structures and later exhumation-related deformation, as well as peak temperatures of 280–290 °C. The Mugitani Complex shares deformation characteristics with both the Shimanto AC and the Sanbagawa MC, and covers the interval from the upper temperatures of the Shimanto AC to the lower temperatures of the Sanbagawa MC. In addition, the two types of deformation differ in their kinematic patterns, suggesting that they took place diachronously in different tectonic settings in the subduction zone. We propose that exhumation-related Sanbagawa deformation occurred in a warm tectonic environment, such as ridge approach to the subduction zone.